KAJIAN EKOLOGIS TERHADAP PEMBANGKIT LISTRIK TENAGA PANAS BUMI DI BEDUGUL, KECAMATAN BATURITI KABUPATEN TABANAN - Wijaya Kusuma, I G. B. (Bumi Lestari; Vol 4 No 2)
Geothermal is one of renewable energy that can be used in electric power plant. Although categorized as safe to the environment, but some parameter should be considered if want to develop as power plant in a big scale. Some aspects should be considered are steam contains and physical characteristic of the steam in the reservoir and the pressure drop in the ground reservoir while using geothermal. If all parameters could be full filled, the geothermal energy can be used as electrical power plant without any complaint.
Keywords: electrical power plant, geothermal, ecological investigation